ANALISIS LOADING TIME HIKITORI MENGGUNAKAN METODE LINE OF BALANCING - Syarah Rizkia Feriaty; Riyaldi Oktapiana; Tri Ngundi Wiyatno (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
In this research, there is a problem about hikitori cycle process through the use of line balancing method, which is able to reduce long loading times become faster. The main objective of this research is to reduce hikitori loading time by using line of balancing, which will later produce new planning with more efficient process. The term hikitori is not common for all industries, but Japanese companies often use naming standards and work culture input in the industry. One of the industries originating from Japan is hikitori, namely vehicles that transport goods that will or have been processed. So that, going through the line balancing stage process makes the hikitori productivity system easier, which happens due to the preparation of the hikitori line with the addition of a new production line with a cycle time of 30 minutes, and the graphic visualization shows the problem where the waiting time becomes 89.5 minutes of the total MP, causing the total actual sigma CT is 323 minutes for a total of 10 MP. The research results show that there is a reduction in job balancing, thereby reducing time to 9 MP and waiting time also decreases to 9 MP or 22 minutes.